Business Confidence and Economic Complexity in Indonesia: Evidence from Technology, Trade, and Research Dimensions - Idroes, Ghalieb Mutig; Wiranatakusuma, Dimas Bagus (Heca Sentra Analitika, 2025)
This study investigates the impact of business confidence on economic complexity in Indonesia, focusing on three key dimensions: research, technology, and trade. Using quarterly data from 2003 to 2021 and applying the Dynamic Ordinary Least Squares (DOLS) estimation method, the analysis incorporates business confidence, economic growth, and gross fixed capital formation as explanatory variables. The DOLS results reveal that an increase in business confidence has a positive and significant effect on technological and trade complexity. However, it is associated with a negative effect on research complexity. Economic growth is positively linked to trade complexity but negatively associated with both technological and research complexity, while gross fixed capital formation contributes positively to technological and research complexity but negatively to trade complexity. These findings highlight the need for integrated policy strategies that align business sentiment and investment behavior with long-term innovation and export development goals in Indonesia.